Risks in Public Administration in the Context of Globalisation - Khadzhyradieva, Svitlana; Chernenko, Nataliia M.; Larina, Nataliya B.; Ruchkina, Marianna M.; Sakaliuk, Oksana O. (International Journal of Criminology and Sociology, 2021)
The relevance of the study is conditioned by the fact that globalisation is accompanied by a conflict of interest, increasing contradictions, the emergence of new risks in various areas of public administration in particular. The paper investigates risks in public administration in the context of globalisation. According to the results of cluster analysis, the risks are grouped into the following clusters: socio-humanitarian, environmental, financial-economic, and information-technological. In the context of the conducted expert assessment, the risks in public administration in the context of globalisation were identified and a cluster analysis of the identified risks was performed; a map of risks is drawn up, and constructive and destructive factors influencing the processes of globalisation are determined. It was argued that the globalisation processes are already irreversible, but countries need to identify risks to minimise or neutralise them, to predict possible threats and consequences, as an indicator of these changes is security. The paper has theoretical and practical significance, because national and state security are leading in public administration, as almost any conflict becomes a global issue.